Vertically optimized phase separation with improved exciton diffusion enables efficient organic solar cells with thick active layers - Cai, Yunhao; Li, Qian; Lu, Guanyu; Ryu, Hwa Sook; Li, Yun; Jin, Hui; Chen, Zhihao; Tang, Zheng; Lu, Guanghao; Hao, Xiaotao; Woo, Han Young; Zhang, Chunfeng; et al. (Nature communications, 2022)
The development of organic solar cells (OSCs) with thick active layers is of crucial importance for the roll-to-roll printing of large-area solar panels. Unfortunately, increasing the active layer thickness usually results in a significant reduction in efficiency. Herein, we fabricated efficient thick-film OSCs with an active layer consisting of one polymer donor and two non-fullerene acceptors. The two acceptors were found to possess enlarged exciton diffusion length in the mixed phase, which is beneficial to exciton generation and dissociation. Additionally, layer by layer approach was employed to optimize the vertical phase separation. Benefiting from the synergetic effects of enlarged exciton diffusion length and graded vertical phase separation, an efficiency of 17.31% (certified value of 16.9%) is obtained for the 300 nm-thick OSC, with a short-circuit current density of 28.36 mA cm −2 , and a high fill factor of 73.0%. Moreover, the device with an active layer thickness of 500 nm also shows an efficiency of 15.21%. This work provides valuable insights into the fabrication of OSCs with thick active layers. Exciton diffusion length and graded vertical phase separation of the active layer play a critical role in the realization of high-performance thick-film organic solar cells (OSCs). Here, authors demonstrated OSCs with an efficiency of 17.31%, with an active layer thickness of around 300 nm.